2013
DOI: 10.7243/2049-9752-2-20
|View full text |Cite
|
Sign up to set email alerts
|

Detection of ventilator associated pneumonia, using clinical pulmonary infection score (CPIS) in critically ill neurological patients

Abstract: Background: Ventilator associated pneumonia (VAP) remains the most common nosocomial infection in the ICU with a very high morbidity, mortality and cost of treatment. Clinical pulmonary infection score (CPIS) can be used prospectively to diagnosis VAP, so as to initiate early treatment and prevent mortality. Most studies indicate that the CPIS has limited value to diagnose VAP. We conducted a prospective study to detect VAP using CPIS score in neurological patients. Materials and Method: After approval of Ethi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2015
2015
2023
2023

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 25 publications
0
4
0
Order By: Relevance
“…the minimum and maximum scores of MCPIS were 0 and 12, respectively. MCPIS over than 7 was diagnostic for VAP ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…the minimum and maximum scores of MCPIS were 0 and 12, respectively. MCPIS over than 7 was diagnostic for VAP ( 19 ).…”
Section: Methodsmentioning
confidence: 99%
“…In addition, the CPIS, a diagnostic algorithm, is mainly applied for ventilator-associated pneumonia and community-acquired pneumonia. Most studies indicated that CPIS had inaccurate sensitivity and speci city [34][35][36][37]. The CPIS was suggested to have high inter-observer variability and is not available for multiple centers study [37,38].…”
Section: Discussionmentioning
confidence: 99%
“…A research by The Canadian Critical Care Trials Group suggests that respondents with the most mechanical ventilators in trauma disease, followed by cardiovascular disease, respiratory disease, and neurological diseases (Group, 2006). Another study stated that most ventilator-installed patients are in cardiovascular system disease (Harde et al, 2013). Another also showed that the most respondents are with cardiovascular system disease (Saragih et al, 2014).…”
Section: Description Of Respondent's Characteristicsmentioning
confidence: 99%